Analysis of Natural Stone Wall Function Index Using Fuzzy Building Service Life (FBSL) - Griselda Junianda Velantika; Ayu Fatimah Sari; Karina Meilawati Eka Putri; Elok Dewi Widowati (Asosiasi Dosen Muda Indonesia, 2026)
Natural stone wall claddings are widely used in residential buildings, but their functional performance often declines earlier than the building’s structural design life due to environmental exposure and installation-related deterioration. Objective: This study aims to quantify the functional condition of natural stone wall claddings using a Function Index (FI) so that maintenance decisions can be made more consistently and objectively. Methodology: A quantitative case-study approach was applied to five residential buildings in Situbondo Regency. Data were collected through field observations and building-age documentation, assessed using expert judgment, and analyzed using a fuzzy inference-based Fuzzy Building Service Life (FBSL) model to obtain a crisp FI score for each building. Findings: The results indicate that one building was classified as moderate/fair (FI = 56), while four buildings were classified as poor (FI = 0–23), implying higher maintenance urgency. When linked to the estimated Remaining Service Life (RSL) under an assumed 50-year design life and a 2020 observation year, an exploratory exponential relationship between FI and RSL was obtained (y = 12.177e0.3243x; R² = 0.7444). Implications: The FI can serve as a practical decision-support indicator to prioritize immediate repair, scheduled maintenance, or routine monitoring for façade components, even when the building still has considerable remaining design life. Originality: This research contributes by integrating a fuzzy-based functional condition index for natural stone claddings with a remaining service life perspective in a residential case-study context, bridging qualitative inspection outcomes with interpretable maintenance planning.